EFEKTIFITAS PERENCANAAN PEMBANGUNAN DAERAH DENGAN PENDEKATAN PARTISIPASI MASYARAKAT DESA - IBRAHIM IBRAHIM; MULIATI MULIATI (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2023)
Based on data from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration, the number of villages in our country is 33,893 villages. This number of villages occupies more than 80% of the territory of the Republic of Indonesia. In an effort to realize the state's goal, namely to improve the welfare of the Indonesian people, the Government pays special attention to existing villages, especially in terms of implementing village development. With the spirit of "nawacita" and the spirit of "autonomy" the government is currently allocating a significant amount of budget to villages so that rural communities can develop their own villages based on needs on a priority scale. With a paradigm leap regarding regional development where community empowerment, especially rural communities, is expected to contribute more to development in their respective villages, it is necessary to review the role of rural communities in the development implementation process starting from the planning, implementation, monitoring and evaluation, supervision and his coaching. This is considered important to do because with the leap, the development paradigm which was originally controlled by the central government has now shifted where the village government and its own community are expected to carry out all development processes so that the output is expected to be able to answer the problems that exist in their respective villages. The most important thing to observe and analyze is the extent of the role and contribution of the community in the rural development process when viewed from the regulations that have been established. This study is an initial study with a theoretical approach that examines existing regulations regarding the village development implementation process and its stages and the consequences that will arise. In the next stage, this study will be carried out in the form of implementation by conducting a study in one of the villages to see the extent of the effectiveness of village development by maximizing the empowerment of village communities and based on the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia Number 21 of 2020 concerning Guidelines General Village Development and Village Community Empowerment. ABSTRAKBerdasar data dari Kementerian Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi jumlah desa di negara kita adalah 33.893 desa. Jumlah desa ini menempati lebih dari 80 % wilayah NKRI. Dalam upaya mewujudkan tujuan negara yaitu untuk mensejahterakan rakya Indonesia maka Pemerintah memberikan perhatian khusus kepada desa-desa yang ada khususnya dalam hal pelaksanaan pembangunan desa. Dengan semangat “nawacita” dan semangat “otonomi” pemerintah dewasa ini mengalokasikan anggaran dengan jumlah yang cukup signifikan ke desa-desa agar masyarakat pedesaan dapat membangun desanya sendiri dengan berdasar pada kebutuhan dengan skala pr=ioritas. Dengan lompatan paradigma tentang pembangunan daerah dimana pemberdayaan masyarakat khususnya masyarakat pedesaan diharapkan dapat berkontribusi lebih besar terhadap pembangunan di desanya masing-masing maka perlu dilakukan peninjauan tentang peranan masyarakat di pedesaan dalam proses pelaksanaan pembangunan mulai dari proses perencanaan, pelaksanaan, pemantauan dan evaluasi, pengawasan serta pembinaannya. Hal ini dianggap penting dilakukan karena dengan lompatan paradigma pembangunan yang semula dikendalikan oleh pemerintah pusat sekarang bergeser dimana pemerintah desa beserta masyarakatnya sendiri diharapkan melakukan semua proses pembangunan sehingga outpunya diharapkan dapat menjawab permasalahan-permasahan yang ada di desanya masing-masing. Hal yang paling penting untuk diamati dan dianalisis adalah sejauh mana peranan dan kontribusi masyarakat dalam proses pembangunan pedesaan apabila ditinjau dari aturan-aturan yang sudah ditetapkan. Kajian kali ini merupakan kajian awal dengan pendekatan teoritik yang mengkaji aturan yang ada tentang proses pelaksanan pembanguna desa dan tahapannya dengan konsekuensi yang akan ditimbulkan. Pada tahapan berikutnya kajian ini akan dibawa dalam bentuk implementasi dengan melakukan kajian pada salah satu desa untuk melihat sejauh mana efektifitas pembangunan desa dengan memaksimalkan pemberdayaan masyarakat desa dan berdasar pada Peraturan Menteri Desa, Pembangunan Daerah Tertinggal, Dan Transmigrasi Republik Indonesia Nomor 21 Tahun 2020 Tentang Pedoman Umum Pembangunan Desa Dan Pemberdayaan Masyarakat Desa.